Strategi Komunikasi Serikat Pekerja Pers dalam Menyelesaikan Konflik Hubungan Industrial di Perusahaan Media - Wildan Hakim (Universitas Multimedia Nusantara, 2016)
he number of press labor union in Indonesia is relatively small. Moreover, not so many unions successfully perform their roles in media companies. This research aims to find the factors which cause the failure of the press labor union. Presumably, press labor unions fail to show their teeth because of the non-existent class consciousness and they chose wrong communication strategy. This study use qualitative approach and interpretive case study method. The factors that determine the success of press labor union will be analyzed through Marx’ theory of class consciousness and the proactive and reactive approaches which used by the union. The result shows that the press labor unions have been implementing common communication strategy, but they have to face organizational problem which affect the communication activities. Keywords: communication strategy, labor union, class consciousness, media economy